1965
DOI: 10.1152/ajplegacy.1965.209.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of circulatory responses to systemic hypoxia in the anesthetized dog

Abstract: The possibility that mechanisms secondary to the increased ventilation may contribute significantly to the circulatory responses to systemic hypoxia was explored in anesthetized dogs. In 14 spontaneously breathing dogs systemic hypoxia induced by breathing 7.5% oxygen in nitrogen increased cardiac output, heart rate, mean arterial blood pressure, and femoral arterial flow, and decreased systemic and hindlimb vascular resistances. In 14 dogs whose ventilation was kept constant by means of a respirator pump and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
1

Year Published

1967
1967
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 0 publications
6
30
0
1
Order By: Relevance
“…Studies in patients with respiratory failure have indicated that hypoxemia, as well as hypercapnia, can induce a fall in SVR and an increase in CO, which sustain adequate tissular oxygenation. [51][52][53] Interpretation of the measurements of DO 2 raised the same observation. In both groups with HH (study group and control group 1), DO 2 measurements that combine CO and arterial saturation in oxygen were very low (median values: 376 mL/min · m 2 in study group and 385 mL/min · m 2 in the control group 1 compared with the normal value 11 of 520 to 720 mL/min · m 2 ), and close to the critical limit of 330 mL/min · m 2 , considered as the lower level of DO 2 for tissular viability in several studies.…”
Section: Discussionsupporting
confidence: 53%
“…Studies in patients with respiratory failure have indicated that hypoxemia, as well as hypercapnia, can induce a fall in SVR and an increase in CO, which sustain adequate tissular oxygenation. [51][52][53] Interpretation of the measurements of DO 2 raised the same observation. In both groups with HH (study group and control group 1), DO 2 measurements that combine CO and arterial saturation in oxygen were very low (median values: 376 mL/min · m 2 in study group and 385 mL/min · m 2 in the control group 1 compared with the normal value 11 of 520 to 720 mL/min · m 2 ), and close to the critical limit of 330 mL/min · m 2 , considered as the lower level of DO 2 for tissular viability in several studies.…”
Section: Discussionsupporting
confidence: 53%
“…Another possible contribution to the tachycardia, increase in cardiac output and decrease in SVR seen with hypoxemia, may arise from lung stretch receptor responses (26). These vagally mediated actions of hyperventilation itself could have contributed to the initial circulatory response to hypoxemia.…”
Section: Resultsmentioning
confidence: 99%
“…Carotid body stimulation by hypoxemic blood results in bradycardia when anes-thetized and paralyzed dogs are mechanically ventilated at a controlled rate (11,12). Cutting the carotid body's nerve eliminates the bradycardia (11, .13 (11).…”
Section: Discussionmentioning
confidence: 99%